Asian smallholders in comparative perspective - Rigg, Jonathan; Gillen, Jamie, 1977-; Thompson, Eric (Eric C.) (Transforming Asia., 2019)
This book provides the first multi-country, inter-disciplinary analysis of the single most important social and economic formation in the Asian countryside: the smallholder. Based on nine core country chapters, the volume will describe and explain the features, evolution, functioning and future of the smallholder and smallholdings across East and Southeast Asia. As well as providing a source book for scholars working on agrarian change in the region, it will also engage with a number of key current areas of debate, including: the nature and direction of the agrarian transition in Asia, and its distinctiveness vis à vis transitions in the global North; the persistence of the smallholder notwithstanding deep and rapid structural change; and the question of the efficiency and productivity of smallholder-based farming set against concerns over global and national food security.